2016
DOI: 10.5037/jomr.2016.7203
|View full text |Cite
|
Sign up to set email alerts
|

Designing for Safety: Implications of a Fifteen Year Review of Swallowed and Aspirated Dentures

Abstract: ObjectivesDentures are worn by around 20% of the population, yet if they become displaced they may enter the gastrointestinal or respiratory system, sometimes with grave consequences. The aim of this study was to review recent published literature in order to identify the epidemiology of patients and characteristics of swallowed and aspirated dental prostheses, and propose strategies to minimise these risks.Material and MethodsA fifteen year retrospective of published case series and case reports was carried o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 68 publications
0
22
0
Order By: Relevance
“…In the present case, the patient experienced two instances of denture displacement, and the dentures became lodged in her hypopharynx and rectum. A previous case series [5] revealed that dentures most commonly become lodged in the esophagus (33 of 83 cases), although other common sites are the hypopharynx or larynx (12 of 83 cases) and the lower gastrointestinal tract (17 of 83 cases). In this case, the newer denture was almost as large as the older one, except that the newer one had a clasp, which could make it stuck in the hypopharynx easier than the older one.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present case, the patient experienced two instances of denture displacement, and the dentures became lodged in her hypopharynx and rectum. A previous case series [5] revealed that dentures most commonly become lodged in the esophagus (33 of 83 cases), although other common sites are the hypopharynx or larynx (12 of 83 cases) and the lower gastrointestinal tract (17 of 83 cases). In this case, the newer denture was almost as large as the older one, except that the newer one had a clasp, which could make it stuck in the hypopharynx easier than the older one.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, dementia can make it difficult or impossible for the patient to alert caregivers to the displaced denture, and the patient may even be unaware of its displacement. For example, the case series [5] revealed that, in only 58% of cases (53/86), the situations that the denture had been displaced were known. Moreover, prolonged denture impaction can increase the likelihood of complications, and early detection with therapeutic management is important for achieving good outcomes [6].…”
Section: Discussionmentioning
confidence: 99%
“…There have been documented cases of iatrogenic foreign bodies in the UADT in both dentistry9 and anaesthesia, including teeth,10 a latex glove11 and a denture that was aspirated into the larynx on intubation, in a case of bilateral maxillary fractures, which sadly ended in fatality after extubation 12. A 15-year review of 83 cases of aspirated dentures identified that in 12 (14%) cases the dentures were found in the hypopharynx or larynx, and in 6 (7%) cases the dentures were aspirated during general anaesthetic 3…”
Section: Discussionmentioning
confidence: 99%
“…Full or partial dentures are used by approximately one in five people aged between 18 and 74 years 1. According to the literature, eating, maxillofacial trauma and dental treatment procedures are the main reasons for an aspirated tooth or denture,2–4 and while ethanol intoxication, dementia, stroke and epilepsy are predisposing factors, the majority of cases occur in patients with no known risks 2 3. Foreign bodies in the upper aerodigestive tract (UADT) can pose a diagnostic challenge, as the delayed symptoms may mimic other common conditions like asthma, recurrent pneumonia, upper respiratory tract infection and persistent cough 5…”
Section: Introductionmentioning
confidence: 99%
“…However, a systematic review by Kent et al evaluated published reports of denture swallowing or aspiration over 15 years and concluded that 56% of patients did not have any predisposing factors. They also noted that most retrieved dentures were damaged or loose [5].…”
Section: Discussionmentioning
confidence: 99%